2014 IEEE Conference on Open Systems (ICOS) 2014
DOI: 10.1109/icos.2014.7042645
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the effectiveness of expectation maximization algorithm for suspicious transaction detection in anti-money laundering

Abstract: Money laundering refers to activities that disguise money receive through illegal operations and make them become legitimate. It leaves serious consequence that may lead to economy corruption. Extensive research has been conducted to investigate proper solution for suspicious transactions detection. In the realm of clustering approaches, traditional research only concentrate on k-means as the best technique so far. On the other hand, although belongs to the same class, there is a lack of studies conducted in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 11 publications
(10 reference statements)
0
13
0
Order By: Relevance
“…In this paper, we have designed and implemented a deep learning model that gives state-of-the-art results, in terms of the FPR, RFT, and AUC, for improving the anti-money laundering (AML) process. We also explored recent state-ofthe-art deep learning and unsupervised learning techniques such as autoencoder (AE), variational autoencoder (VAE), and generative adversarial network (GAN), and we showed that these techniques can enhance earlier results [7,8].…”
Section: E Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, we have designed and implemented a deep learning model that gives state-of-the-art results, in terms of the FPR, RFT, and AUC, for improving the anti-money laundering (AML) process. We also explored recent state-ofthe-art deep learning and unsupervised learning techniques such as autoencoder (AE), variational autoencoder (VAE), and generative adversarial network (GAN), and we showed that these techniques can enhance earlier results [7,8].…”
Section: E Discussionmentioning
confidence: 99%
“…The data is obtained from the research project that was undertaken in 2014 between the School of Computer Science, University of Nottingham (Malaysia campus) and a local Malaysian Bank. The original dataset that was obtained in 2014 contains about 30 million transactions (records) for the period from 2012 until 2013 [7]. However, for privacy reasons, the full dataset is not accessible anymore.…”
Section: ) Raw Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in [11]- [13] applied a cluster-based approach consisting of unsupervised learning techniques such as k-means [14]. Chen et al [15] improved existing outlier detection results with expectation-maximization technique [16]. Unlike the general approach to cluster the customers, Soltani et al [17] cluster the transactions and detect money laundering activities according to structural similarity.…”
Section: State Of the Art A Data Science Approachesmentioning
confidence: 99%
“…Connected Smart Cities 2020; and Web Based Communities and Social Media 2020 criterion for validating clusters after clustering. (Chen et al, 2014) Examined the use of expectation maximization for detecting suspicious financial transaction with 30 million transactions from local X bank in Malaysia. The results show that Expectation Maximization (EM) defeated traditional clustering method k -means for AML in detecting true suspicious transactions with low false positive rate, giving the advantage to EM to be employed in this field.…”
Section: Literature Reviewmentioning
confidence: 99%